Current status and future prospective of bluefin tuna (Thunnus thynnus orientalis) farming in Mexico and the West Coast of the United States - Sylvia P.; Belle S.; Smart A. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
This paper provides a brief summary of the history of tuna farming in Mexico and the United States as well as future prospects for tuna farming in both countries. Production and growth performance data from a Mexican farming operation are discussed for bluefin, bigeye and yellowfin tuna. The domestic and international market situation is also reviewed. Due to the lack of quota regulations, increased national and international interests and the development of a more skilled workforce for these types of operations, both Mexico and the US are uniquely poised to expand and contribute more significantly to worldwide tuna farming production.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)